Pengembangan Media Komik dengan Nilai Karakter pada Materi Sumpah Pemuda Kelas V di SDN 2 Kelekar - Rizal, Samsu; Arafat, Yasir; Heldayani, Eni (Jurnal Ilmiah Dikdaya, 2024)
This research aims to produce comic civics learning media on youth oath material in Class V Elementary Schools that is valid and practical. This research uses the Research and Development method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of data analysis show that the comic media developed is in the "very valid" category based on a validation questionnaire sheet from 3 experts which includes content, construct and language with an average validity value of 85.97% and the comic media developed is in the "very practical" category. based on the student response questionnaire sheet with an average of 93.62%. Based on these results, it shows that the comic products that have been developed are suitable for use in the learning process.